Association Between Obesity and the Incidence of Hypertension Among Adolescents in Ponorogo - Ulfa, MH Muflihatul; Greta Perdana Putri,, Rachma; Fadhila, Rais (Universitas Ahmad Dahlan, 2025)
Obesity occurs due to excess energy stored in body fat tissue, resulting from an imbalance between energy intake and expenditure. In adolescence, obesity is a multifactorial health problem influenced by genetic, behavioral, environmental, and social factors, and is a known risk factor for hypertension. The pathogenesis of hypertension in obese individuals involves abnormal adipose tissue activity in producing hormones and adipokines, although the mechanisms are not yet fully understood. Several studies have linked obesity to hypertension, but mostly in adult populations, where the indicators for obesity differ from those for adolescents and children. In younger populations, overweight or obesity assessment should be based on BMI-for-age charts adjusted for sex, yet studies in adolescents often still use adult criteria. This study aimed to determine the association between obesity and hypertension among adolescents in Ponorogo. An observational analytic study with a cross-sectional design was conducted using data from the 2024 PASHMINA (Pelayanan Kesehatan Remaja Milik NA) health screening program organized by Regional Board of Nasyiatul Aisyiyah of Ponorogo among senior high school students. A total of 179 respondents participated, with 65.9% female and 65.4% having normal nutritional status. The overall prevalence of hypertension was 6.1%, while obesity prevalence was 12.8%. Hypertension was more common in obese adolescents (26.1%) compared to non-obese adolescents (3.2%), with obesity increasing the risk of hypertension by 10.66 times (p < 0.001). These findings highlight the need for appropriate obesity assessment methods in adolescents and the importance of nutrition education, promotion of physical activity, early detection, and regular health monitoring to prevent hypertension from an early age.